1970
DOI: 10.1093/bja/42.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Pharmacology of Local Anaesthetic Agents

Abstract: Site of action of local anaesthetic FIG. 1 The nerve impulse is transmitted from one node of Ranvier to the other. Local anaesthetics prevent the process of depolarization by blocking the ion transmission through the nerve membrane. (After Ward and Benveniste, 1968.) B. LOFSTROM, MJ)., Head of the Department of Anaesthesia and Assistant Professor at the Karolinska Institute, Stockholm, Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…In that paper, the authors reported that 2% lidocaine produced faster onset of action and longer duration than 1% lidocaine 11 . It is believed that the concentration of the local anesthetic used has an influence on the absorption capacity at the perineural level, obeying Fick's principle 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In that paper, the authors reported that 2% lidocaine produced faster onset of action and longer duration than 1% lidocaine 11 . It is believed that the concentration of the local anesthetic used has an influence on the absorption capacity at the perineural level, obeying Fick's principle 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Since adrenalin prolongs the duration of action of mepivacaine by about 100 O/o (Lofstrom 1970), presumably bupivacaine has a duration of action about four times as long as that of mepivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…A longer onset time, particularly as concerns the blocking of motor impulses after bupivacaine, has been observed by Bromage (1969). According to Lofstrom (1970), this tendency of bupivacaine may be an expression of lesser potency. It needs also to be taken into account that in the present series the mean weight of the patients in the mepivacaine group was lower than in either bupivacaine group, with the consequence that the dose of mepivacaine was correspondingly larger and thus the onset time possibly was shortened for that reason.…”
Section: Discussionmentioning
confidence: 99%
“…30 Carbonated solutions, which release carbon dioxide and rapidly lower intracellular pH, will cause increased dissociation of the analgesic base into the ionised form. The blood dissociation constant (pKa) of most local analgesics is in the region of 8-9, but they are prepared in solutions with a pH much lower than this, so that considerable buffering has to occur in the tissues to release free base.…”
Section: Local Analgesic Solutionsmentioning
confidence: 99%